Gender Differences in Preferences for Meaning at Work - Vanessa Burbano; Nicolas Padilla; Stephan Meier (Institute of Labor Economics (IZA), 2020)
In an effort to better understand occupational segregation by gender, scholars have begun to examine gender differences in preferences for job characteristics. We contend that a critical job characteristic has been overlooked to date: meaning at work; and in particular, meaning at work induced by job mission. We provide empirical evidence of the importance of gender differences in preferences for meaning at work using mixed methods. First, we demonstrate the universality of gender differences in preferences for meaning at work using a cross-country survey covering individuals in 47 countries. We show that these differences become more pronounced with greater levels of education and economic development, suggesting that their importance is likely to increase over time. To address potential social desirability bias in responses about job preferences and to examine whether differences in preferences translate into differences in important behavioral outcomes, we next conduct a conjoint analysis of a cohort of MBA students at a top US university and track their behavior over two years. We show show that preferences for meaning at work, particularly meaning induced by job mission, explain gender differences in not only types of courses taken, but also job industry placement during and after the MBA, thus helping to explain the under-representation of females in higher-paying industries. Overall, this research establishes that men and women differ in their preferences for meaning at work, with important implications for our understanding of the drivers of occupational segregation and of the consequences of corporate mission and purpose.
Keywords: D91; J16; 330; job design; job preferences; gender segregation by occupation; mission; meaning at work